Optimasi Ekonomi Berkelanjutan UMKM Kelurahan Gunung Anyar Tambak melalui Sosialisasi dan Pendampingan Sertifikasi Halal - Putri, Devita Wahyu Aulia; Sholihah, Dewi Deniaty (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the local economic growth in the Gunung Anyar Tambak Village. Halal certification plays an important role in maintaining business sustainability, increasing market access, competitiveness, product value added, as well as obtaining financing and government support. However, many MSMEs in Gunung Anyar Tambak Village do not yet have halal certification for their food products. This activity aims to increase understanding and mentoring as an effort to optimize sustainable economic growth of MSMEs. Halal certification also supports the SDGs goal number 8 on sustainable economic growth. With halal certification mentoring, it is hoped that MSMEs can improve competitiveness, reach more marketers, and contribute to inclusive and sustainable economic growth.